The narrow vesicourethral angle measured on postoperative cystography can predict urinary incontinence after robot-assisted laparoscopic radical prostatectomy. (4th March 2018) - Sugi, Motohiko; Kinoshita, Hidefumi; Yoshida, Takashi; Taniguchi, Hisanori; Mishima, Takao; Yoshida, Kenji; Yanishi, Masaaki; Komai, Yoshihiro; Watanabe, Masato; Matsuda, Tadashi
Abstract: Objective: Radical prostatectomy is associated with complications including urinary incontinence. A significant association between specific features of the vesicourethral anastomosis and urinary incontinence after radical prostatectomy has been demonstrated. The aim of this study was to identify the most useful predictor of postoperative urinary incontinence after robot-assisted laparoscopic radical prostatectomy (RALP) according to the features of the vesicourethral anastomosis as determined by postoperative cystography. Materials and methods: The final study cohort consisted of 150 patients. Postoperative cystography was performed within 1 week after RALP. The ratio between the longitudinal and horizontal lengths (L/H) of the bladder, the position of the urethrovesical junction (UVJ) and the bladder neck angle as seen on the cystogram were evaluated. Postoperative continence status was evaluated by a 1 h pad test 1 day after catheter removal and by the use of safety pads, retrieved retrospectively from patient records. The association between these variables and urinary incontinence was then analyzed. All patients were followed for at least 1 year postoperatively. Results: The continence rates on the 1 h pad test and 1 month and 1 year after RALP were 31.3%, 56% and 93.3%, respectively. In multivariate analyses, urinary incontinence was significantly associated with nerve sparing, L/H and the vesical angle as determined on the 1 h pad test, but only with the vesical angle at 1 month and 1 year postoperatively. Conclusion: A narrow vesical angle measured on cystography is a useful predictor of postoperative urinary incontinence after RALP.